Factors that Affect the Income of Artisan Palm Sugar Maker in Candimulyo - Dyah Rasti; Agus Setiadi; Kustopo Budiraharjo (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
This study aimed to analyze the income and factors affecting the income of the artisan palm sugar maker in a Women Farmer Group (WFG) in Candimulyo District, Magelang Regency named Srikandi. This study done from November 17th to December 15th, 2019 in Srikandi WFG, Kebonrejo Village, Candimulyo District, Magelang Regency. This study was employing a census method with a total of 33 artisan palm sugar maker. The data collection done by interview, observation, and literature review technique. Data analyzed by the production cost, revenue and income, and multiple linear regression analysis. Results showed that mean sugar palm production, mean production cost, mean revenue, or mean income was 2.89 kg/production/day, IDR 34,225.91/production volume/day, IDR 49,068.18/production volume/day, and IDR 14,942.27/production volume/day. The multiple linear regression analysis equation was Y= 1009.844 + 979.915X1 – 17798.012X2 + 9330.432X3 – 0.704X4 + e. The factor of additional material, worker utilization, production, and fuel cost simultaneously affected the income. Partially, the worker utilization, production, and fuel cost affected the income, while the amount of the additional material didn’t affect the income partially.